(untitled) (Journal of Education and Development, 2018)
The purpose of this study was to manage each course in the spectrum of curriculum and to monitor the students’ individual sequential performances. We developed a relational database containing data on learning outcomes, computer-based test results, tutors, and students. In addition, we restructured the students’ test results in terms of learning outcomes to produce competency portfolios of individual students. We found that test reliabilities were variable among the courses. Reuse of test items significantly increased the difficulty and compromised the discrimination of items. By building the relationships among the items, the test results and learning outcomes helped us to monitor and manage each test. And it provided not only the students’ status but their sequential changes. This made it possible to clearly visualize each individual student’s current and past competencies. By building the relational database, we could evaluate diverse aspects of our curriculum and we got an idea to improve it. The database will help us to guide data-driven curriculum management to complement pedagogy-driven medical education. This would be an effective tool to manage undergraduate medical education in an integrated manner.